Isolation and characterisation of novel enzymes producing fructo- and galacto-oligosaccharides through a metagenomic approach - Smith, Marthinus Luther (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.